Self-assembly of DNA-polymer complexes using template polymerization. - Trubetskoy, V S (1998)
The self-assembly of supramolecular complexes of nucleic acids and polymers is of relevance to several biological processes including viral and chromatin formation as well as gene therapy vector design. We now show that template polymerization facilitates condensation of DNA into particles that are <150 nm in diameter. Inclusion of a poly(ethylene glycol)-containing monomer prevents aggregation of these particles. The DNA within the particles remains biologically active and can express foreign genes in cells. The formation or breakage of covalent bonds has until now not been employed to compact DNA into artificial particles.